Green chromatographic approach to determine methocarbamol, aspirin and their related impurities in their combined pharmaceutical formulation and human plasma: with computational evaluation - Yasmine F. Bassuoni; Asmaa M. AboulMagd; Maha M. Ibrahim (BMC Chemistry)
Abstract Nowadays, one of the main objectives is to protect the environment and reduce the adverse impacts of chemicals on it. One of the most difficult issues for researchers is determining the efficiency and quality of the suggested approach in terms of environmental and human safety. The present research presents advanced, accurate, green high-performance liquid chromatographic method (HPLC) to estimate a combination of methocarbamol (MET) and aspirin (ASP) as well as their related impurities, guaifenesin (GUF) and salicylic acid (SA), respectively, with low retention time and ideal separation. Chromatographic separation was performed on X-Bridge C8 reversed phase (RP) column (4.6 × 250 mm, 5 μm particle size) utilizing methanol: water: triethylamine (70:30, 0.1% by volume) at pH 3.00 by o-phosphoric acid as a mobile phase with 2.00 mL min−1 flow rate at 254.00 nm. The proposed method succeeded to achieve linearity over a concentration ranges of 0.30–50.00 μg mL−1, 1.00–300.00 μg mL−1, 10.00–500.00 μg mL−1 and 0.10–50.00 μg mL−1 for GUF, MET, ASP and SA, respectively. All the developed results were validated in compliance with the International Council of Harmonization (ICH) instructions. The suggested method was successfully applied to assess MET and ASP in their pharmaceutical formulation and in spiked human plasma. The molecular docking approach was employed to evaluate how the two drugs and their related impurities interacted with the stationary phase and to predict the suggested sequence of elution. The greenness of the developed analytical method was evaluated using whiteness assessment and two green approaches; analytical eco-scale and AGREE. The proposed method proved not only to be green, time-saving and more sensitive for the routine analysis of MET and ASP in QC laboratories, but also it can effectively handle the presence of impurities such as GUF and SA. Graphical Abstract